2021
DOI: 10.1002/er.6702
|View full text |Cite
|
Sign up to set email alerts
|

The examination of performance characteristics of a beta‐type Stirling engine with a rhombic mechanism: The influence of various working fluids and displacer piston materials

Abstract: In this study, to develop a power generation system that can use renewable energy resources more efficiently, a beta-type Stirling engine with rhombic mechanism was designed and manufactured. Kinematic and thermodynamic analyses of a beta-type Stirling engine were performed numerically in the Fortran program.Volume and pressure changes depending on crankshaft angle of Stirling engine were made using the isothermal analysis. The effects of the basic parameters related to engine performance, such as working flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…According to the values acquired in the tests carried out by O ¨zgo¨ren and C xetinkaya, 30 they determined that the power values of air and helium working fluids were similar to each other, and although the power values were different due to different engine types and sizes, the power values were higher in the tests with helium. In the study by Erol and C xalıs xkan, 46,47 it was indicated that the working fluid had significant impacts on engine performance characteristics. It was stated that reducing losses in the amount of heat transferred to the engine body and working fluid in the heater in Stirling engines would positively affect engine power.…”
Section: Resultsmentioning
confidence: 99%
“…According to the values acquired in the tests carried out by O ¨zgo¨ren and C xetinkaya, 30 they determined that the power values of air and helium working fluids were similar to each other, and although the power values were different due to different engine types and sizes, the power values were higher in the tests with helium. In the study by Erol and C xalıs xkan, 46,47 it was indicated that the working fluid had significant impacts on engine performance characteristics. It was stated that reducing losses in the amount of heat transferred to the engine body and working fluid in the heater in Stirling engines would positively affect engine power.…”
Section: Resultsmentioning
confidence: 99%
“…They computed the total exergy efficiency of the system as 64.26%. Erol and C xalıs xkan 33 and Erol et al 34 determined the impacts of two displacer pistons made of different materials on the engine performance characteristics of a b-type Stirling engine with a cylinder volume of 365 cm 3 using helium, nitrogen, air, carbon dioxide, and argon gases as working fluids by employing the thermodynamic analysis method. As a result, they demonstrated that the best engine performance conditions were acquired when a stainless steel displacer piston was used at a charge pressure of 4 bar and an engine speed of 550 rpm with helium as the working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…42 The influence of working mediums and the material of the displacer piston to the performance was also investigated. 43,44 Rogdakis et al 45 introduced a numerical time-dependent model based on nodal analysis. The model took into account the convective heat transfer between the gas and the cylinder walls, the metal matrix temperature of the regenerator which varies spatially and temporally, the variation of the working medium pressure and the pressure drop due to friction losses as well as the pressure drop in the buffer space.…”
Section: Introductionmentioning
confidence: 99%